Effects of Rosin Powder Application on the Frictional Behavior Between a Finger Pad and Baseball - Yamaguchi, Takeshi (Front Sports Act Living, 2020)
Rosin powder, which is composed of magnesium carbonate powder and pine resin, is often used as a grip-enhancing agent in baseball pitching. However, the effect of rosin powder on friction at the baseball–human finger interface remains unclear. This study aimed to investigate the effect of rosin powder on the friction coefficient between a baseball and a finger using sliding friction tests. Ten young adult males participated in this study who were asked to slide the index finger of their dominant hand over the leather skin of a baseball adhered to the force sensor, which was not a real baseball pitching situation. Our findings suggest that rosin powder application stabilizes friction under both dry and wet conditions; that is there was less dependence of the friction coefficient on the normal force and less variation in the friction coefficient among individuals. For most participants, the friction coefficient was not necessarily increased by the presence of rosin powder at the finger pad–leather sheet interface under dry conditions. However, under wet conditions, rosin powder application increased the friction coefficient compared with the non-powdered condition in the large normal force condition, indicating the efficacy of rosin powder as a grip-enhancing agent.